Perbandingan Penerapan Pendidikan Karakter Di Sekolah Yang Ada Di Jepang Dengan Program Jabar Masagi - Tampubolon, Andy Darma Stefanus; Arfianty, Rani (Undiksha Press, 2024)
This research describes and compares the implementation of character education in West Java through the Jabar Masagi program and in Japan. The Jabar Masagi program emphasizes Sundanese values, such as religiosity and cultural awareness, with a focus on four core values: Surti, Harti, Bukti, and Bakti. Meanwhile, character education in Japan encompasses four aspects: Regarding Self, Relation to Others, Relation to Nature and the Sublime, and Relation to Group and Society. Despite differences in focus and activities, both demonstrate similarities in collaborative approaches and environmental appreciation. This research provides insights into effective and culturally relevant character education approaches. The findings contribute to the development of improved character education programs in Indonesia.